2016
DOI: 10.1111/tpj.13224
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for flap endonuclease 1 (FEN1) to maintain genomic stability and transcriptional gene silencing in Arabidopsis

Abstract: SUMMARY As a central component in the maturation of Okazaki fragments, flap endonuclease 1 (FEN1) removes the 5′-flap and maintains genomic stability. Here, FEN1 was cloned as a suppressor of transcriptional gene silencing (TGS) from a forward genetic screen. FEN1 is abundant in the root and shoot apical meristems and FEN1-GFP shows a nucleolus-localized signal in tobacco cells. The Arabidopsis fen1-1 mutant is hypersensitive to methyl methanesulfonate and shows reduced telomere length. Interestingly, genome-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…These results indicate that ZDP and APE2, two BER proteins, play overlapping roles in the maintenance of nuclear genome stability. Similar constitutive activation of the DDR was found in plants with mutations in proteins involved in DNA repair, including ASYMMETRIC LEAVES1/2 ENHANCER7 (Luo et al, 2012), the largest subunit of replication factor C (RFC1) (Liu et al, 2010b), POLα/ICU2, a catalytic subunit of DNA polymerase α (Liu et al, 2010a), POLD2, the second small subunit of DNA polymerase δ (Zhang et al, 2016b), ABO4/ POL2a/TIL1, a catalytic subunit of DNA polymerase ε (Yin et al, 2009), and FLAP ENDONUCLEASE1 (Zhang et al, 2016a). The strong similarity in the effects of mutating these DNA repair proteins and those produced by mutating ZDP and APE2 suggest that these proteins may function in the same pathway.…”
Section: Ape2 and Zdp Play Overlapping Roles In Dna Repairmentioning
confidence: 55%
“…These results indicate that ZDP and APE2, two BER proteins, play overlapping roles in the maintenance of nuclear genome stability. Similar constitutive activation of the DDR was found in plants with mutations in proteins involved in DNA repair, including ASYMMETRIC LEAVES1/2 ENHANCER7 (Luo et al, 2012), the largest subunit of replication factor C (RFC1) (Liu et al, 2010b), POLα/ICU2, a catalytic subunit of DNA polymerase α (Liu et al, 2010a), POLD2, the second small subunit of DNA polymerase δ (Zhang et al, 2016b), ABO4/ POL2a/TIL1, a catalytic subunit of DNA polymerase ε (Yin et al, 2009), and FLAP ENDONUCLEASE1 (Zhang et al, 2016a). The strong similarity in the effects of mutating these DNA repair proteins and those produced by mutating ZDP and APE2 suggest that these proteins may function in the same pathway.…”
Section: Ape2 and Zdp Play Overlapping Roles In Dna Repairmentioning
confidence: 55%
“…Several studies reported TE silencing defects in replisome-related mutants and in plants treated with DNA-damaging agents, where replication is expectedly disturbed (5,(13)(14)(15)(16)(17)(18)(19)(20). We show that HU can alleviate TE silencing but does not enhance pol2a-induced release of silencing (fig 6G), which points to replicative stress as a cause of loss of TE silencing in pol2a mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in several DNA replication-related genes have been reported to destabilize silencing of transgenes and selected endogenous loci in Arabidopsis. These mutations include mutations in the replication protein A2A (RPA2A), the DNA replication factor C1 (RFC1), the flap endonuclease 1 (FEN1), the topoisomerase VI subunit MIDGET, the FAS1 and FAS2 components of the Chromatin assembly factor 1 (CAF-1), as well as mutations in subunits of the three replicative DNA polymerases (Pol), Pol alpha (α), delta (δ) and epsilon (ε) (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the XPG (Xeroderma Pigmentosum Complementation Group G) N-terminal domain and the XPG Internal-region seem to be conserved ( S4A Fig). In Arabidopsis, FEN1 is essential for genome stability, development, and transcriptional gene silencing [101,102]. Nevertheless, FEN1-B proteins seem to fulfill distinct functions besides their regulatory role in cell proliferation [61].…”
Section: Plos Onementioning
confidence: 99%